2016
DOI: 10.1038/srep39152
|View full text |Cite
|
Sign up to set email alerts
|

Implications for management and conservation of the population genetic structure of the wedge clam Donax trunculus across two biogeographic boundaries

Abstract: In a resource management perspective, the understanding of the relative influence of the physical factors on species connectivity remains a major challenge and is also of great ecological and conservation biology interest. Despite the overfishing threat on the wedge clam Donax trunculus in Europe, relatively little information is known about its population genetic structure and connectivity and their consequences on conservation policies. We employed 16 microsatellite loci to characterise the genetic diversity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 66 publications
4
23
0
Order By: Relevance
“…Globally, both markers analysed revealed high genetic diversity in D. trunculus in line with previous studies based on microsatellites (Marie et al, ; Nantón et al, ). Based on the 16S gene, the F type revealed abundant haplotype diversity (0.679) and low levels of nucleotide diversity (0.0046).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Globally, both markers analysed revealed high genetic diversity in D. trunculus in line with previous studies based on microsatellites (Marie et al, ; Nantón et al, ). Based on the 16S gene, the F type revealed abundant haplotype diversity (0.679) and low levels of nucleotide diversity (0.0046).…”
Section: Discussionsupporting
confidence: 89%
“…However, pairwise F ST using the M combined sequences displayed three groups: the Mediterranean group (GA, DE, MA), the Atlantic group (all localities on the coast of the Atlantic Ocean), and the Alboran group (FU). The population structure proposed in this study (three groups: Atlantic, Mediterranean, and Alboran) was observed previously using microsatellite markers (Marie et al, ; Nantón et al, ). The existence of two independently evolving mitochondrial lineages should be considered when population structure studies are carried out in species with DUI.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations